THE EFFECT OF BURNOUT ON EMPLOYEE PERFORMANCE WITH WORKLOAD AS A MODERATING VARIABLE - Idrus, Syech; Pulungan, Delyana Rahmawany; Muliany, Febriyan; Irdhayanti, Efa (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This research is a quantitative study with an explanatory approach. The data used in this study use primary data that researchers obtained from 500 MDP Store employees spread throughout Indonesia obtained by means of an online questionnaire and sent via the respondents' WhatsApp accounts. The questionnaire contains 5 statements, namely strongly agree statements, agree statements, normal/so-so statements, disagree statements, and strongly disagree statements on the 10 questionnaires submitted. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that each hypothesis used in this article can be accepted and proven, namely that the Job Saturation variable can affect Employee Performance and the Workload variable can strengthen the influence of the Job Satisfaction variable on Employee Performance. Based on the results of the third table of the Path Coefficient above, it shows that the Burn Out variable can have an influence on Employee Performance, but it is negative because the T-Statistic value is above 1,960 but negative, namely -6,782 and the P-Values are below the significance level of 0.05, namely 0.036. From these results, it can be concluded that the more bored employees are at work, the more employee performance will decrease or erode.. In addition, in the next row, the Workload variable can strengthen the influence of Job Saturation on Employee Performance in a negative direction because the T-Statistic value is above 1.960, which is -10.232 and the P-Values are below the significance level of 0.05, which is 0.000. This means that the more Employee Workload can make employees more bored in working so that Employee Performance can decrease. Thus, the first and second hypotheses in this article can be accepted. Keywords: Burnout, Employee Performance. Workload